Influence of resistance training rest interval on aerobic fitness, strength and repeated-sprint ability - Bishop, D.; Hill-Hass, S.; Edge, J.; Dawson, B.; Goodman, C. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Previous research has shown that resistance training (RT) can improve strength and single-sprint performance [2]. However, it has previously been shown that there is a negative relationship between peak power on the first sprint and subsequent sprint decrement [1]. Therefore, an increase in peak power may not improve repeated-sprint ability (RSA). The purpose of this study was to investigate the effects of RT on RSA. In addition, we investigated the influence of rest interval between repetitions on adaptations to RT. Methods Eighteen active females were matched and the matched pairs randomly placed into one of two groups that trained 3 x per wk for 5 wks. Both group performed 2-5 sets of 10 exercises at an intensity of 15-20 RM (with 40 s lifting time). The workloads (i.e., resistance and repetitions) were identical for matched pairs, but the rest interval between sets was 20 s for the RT20 group and 80 s for the RT80 group. Prior to and after the training period, both groups performed a seated leg press test (3 RM) and a RSA test (5x6-s cycle sprints every 30 s) followed three days later by a graded exercise test to determine VO2peak and lactate threshold (LT). Results There was a 19.6% increase in strength for the RT20 group (92.7 ± 10.4 to 110.9 ± 9.7 kg, P=0.06, effect size (ES) = 0.56) and a 45.9% increase for the RT80 group (98.8 ± 10.6 to 144.1 ± 9.7 kg, p<0.05). The RT80 group also had a significantly greater improvement in leg strength post training when compared with the RT20 group (P<0.05). Following training, there was no significant change in either V,&O2peak (RT20: 46.1 ± 1.2 to 45.7 ± 1.9 mL·kg.-1·min-1; RT80: 48.7 ± 2.2 to 46.5 ± 2.2 mL·kg.-1·min-1; P>0.05) or the LT (RT20: 124.3 ± 5.2 to 134.4 ± 6.7 W; RT80: 131.9 ± 11.0 to 139.5 ± 12.0 W; P>0.05). There was however, a significant increase in total work completed (J) during the RSA test for both groups following training. There was a 12.5% increase for the RT20 group (17333.4 ± 2236.5 J to 19499.8 ± 1482.5 J, p<0.05) and a 5.4% increase for the RT80 group (17568.6 ± 2462.3 J to 18515.3 ± 2577.8 J, p<0.05). The RT20 group did not have a significantly greater improvement in total work completed post training when compared with the RT80 group, but a trend was indicated by a moderate ES of 0.42 (Graph 2). Discussion / Conclusions We have shown for the first time that high repetition resistance training can significantly improved RSA. However, there was a trend towards a greater improvement in RSA after RT20 as compared to RT80. In contrast, there was a significantly greater improvement in leg strength post training for the RT80 compared to the RT20 group. These results suggest that RT incorporating short rest intervals between sets may compromise leg strength gains. While more research is needed, it is possible that incomplete neurological recovery (resulting in sub-optimal motor unit recruitment) and/or excess H+ accumulation impedes adaptations to resistance training. No significant changes in V,&O2peak or LT were evident following training in either group. This suggests that improvements in RSA can occur without increases in aerobic fitness.